2015
DOI: 10.3390/ijms16023740
|View full text |Cite
|
Sign up to set email alerts
|

Coronary CT Angiography in Managing Atherosclerosis

Abstract: Invasive coronary angiography (ICA) was the only method to image coronary arteries for a long time and is still the gold-standard. Technology of noninvasive imaging by coronary computed-tomography angiography (CCTA) has experienced remarkable progress during the last two decades. It is possible to visualize atherosclerotic lesions in the vessel wall in contrast to “lumenography” performed by ICA. Coronary artery disease can be ruled out by CCTA with excellent accuracy. The degree of stenoses is, however, often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 79 publications
2
35
0
Order By: Relevance
“…17 These are limited because early lesions tend to bulge to the outside of the artery, whereas CT and MRI image the lumen. 18 Quantification of coronary artery calcium (CAC) score by CT has been used since the 1990s with success to diagnose subclinical atherosclerosis. 19 However, CAC scores cannot identify where at-risk lesions are located or the number and size of those that are present.…”
Section: Nonnanoparticle Detection and Treatment Methods For Atheroscmentioning
confidence: 99%
“…17 These are limited because early lesions tend to bulge to the outside of the artery, whereas CT and MRI image the lumen. 18 Quantification of coronary artery calcium (CAC) score by CT has been used since the 1990s with success to diagnose subclinical atherosclerosis. 19 However, CAC scores cannot identify where at-risk lesions are located or the number and size of those that are present.…”
Section: Nonnanoparticle Detection and Treatment Methods For Atheroscmentioning
confidence: 99%
“…(37) It has been widely demonstrated that the sensitivity of CCTA in identifying severe stenosis is very high; on the contrary, the specificity tends to be lower due to the tendency of CCTA to overestimate stenosis, especially in calcified plaques. (24) CCTA is, in fact, indicated for patients with low-to-intermediate risk of CAD because a negative result could exclude, with significant probability, the presence of CAD. Equally, in patients at high risk for CAD, CCTA is unnecessary not only because it cannot add any information to the high pretest probability of CAD, but also as it may require a subsequent coronary angiography, which is still considered to be the gold standard for the identification of coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…(23) In particular, the risk of developing cardiovascular events has been shown to increase significantly when the Agatston score exceeds a value of 400. (24) In our study, in accordance with standardised protocols, CACS was performed prior to coronary angiography. In fact, calcified atherosclerotic plaques can be displayed on CCTA even without the use of endovenous contrast agents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plaques can be classified in three groups: calcified, non-calcified, and mixed (partially calcified). 19 CCTA underestimates the size of the non-calcified plaques and overestimates the size of calcified ones. For example, a plaque that contains a high percentage of fibrosis has high attenuation on CCTA; on the other hand, necrotic areas in the myocardium are characterized by a low attenuation.…”
Section: Cmr Versus Msct Coronary Angiographymentioning
confidence: 99%